Italian post-neorealist cinema - Barattoni, Luca (Traditions in world cinema., 2012)
Unlike countries such as France, the Czech Republic or Brazil, Italy did not have a new wave properly understood as a movement. However, while new artistic schools were emerging in many other countries, Italy was undergoing its most dramatic social and economic transformations. Those violent changes, together with the perceived necessity of renewing the aesthetic heritage of Neorealism, sparked a drastic regeneration of the cinematic language and marked the most memorable period of Italian film history. Italian Post-Neorealist Cinema explores the ferments of Italian cinema from the mid-50s to the end of the 60s, situating its wealth in the context of other national cinemas emerging at the same time. Olmi, Pasolini, Antonioni, Fellini, Visconti, the Taviani Brothers, Cavani, Rosi, Ferreri and many others all made their debut or directed their most representative works during the period. The book brings to the surface the lines of experimentation and artistic renewal appearing after the exhaustion of Neorealism, mapping complex areas of interest such as the emergence of ethical concerns, the relationship between ideology and representation, and the role of Italian counter-culture.